2017
DOI: 10.18805/ijar.v0iof.8456
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and characterization of chitin, chitosan and chitooligosaccharides from crab shell waste

Abstract: An experiment was carried out to utilize the crab shell waste for the production of chitin by chemical extraction method. The obtained chitin was processed to make the more useful compound chitosan by deacetylation of chitin using strong NaOH solution at high temperature. Yield of chitin and chitosan from crab shell waste was found to be 12.2 % and 10.54 %, respectively. Chitosan was further used to produce chito-oligosaccharides (COS) by acid hydrolysis using 0.5 N H 2 SO 4 , 1N H 2 SO 4 and 7N HCl at hourly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 37 publications
2
6
1
Order By: Relevance
“…In our experiment results of 1.0 N solution of HCl for demineralization, 2 N for deproteination and 12.5 N NaOH solutions for deacetylation at a solid to solvent ratio of 1:15, clearly demonstrate a significant yield of chitin and chitosan. Recovery of chitosan in the present study is similar to chitosan yield (15%) from shrimp shell waste reported by and slightly higher than yield of chitosan (12%) in study of [16,17].…”
Section: Discussionsupporting
confidence: 87%
“…In our experiment results of 1.0 N solution of HCl for demineralization, 2 N for deproteination and 12.5 N NaOH solutions for deacetylation at a solid to solvent ratio of 1:15, clearly demonstrate a significant yield of chitin and chitosan. Recovery of chitosan in the present study is similar to chitosan yield (15%) from shrimp shell waste reported by and slightly higher than yield of chitosan (12%) in study of [16,17].…”
Section: Discussionsupporting
confidence: 87%
“…While the peak of chitin on crab shells in the Sfax market, Tunisia was shown at 3447 cm −1 (O-H), 3,267-3,104 cm −1 (N-H stretching) and 2,929-2,882 cm −1 (asymmetrical and symmetrical C-H) (Hajji et al, 2015). The peak of chitin in crab shell samples from the Russel fish market, India was at 3,443 cm −1 (O-H stretching), 3,107 cm −1 (N-H stretching), 1,558 cm −1 (amide II), 1,314 cm −1 (amide III), 1,028 cm −1 (C-O stretching) (Varun et al, 2017). Another sign that the compound contains chitin are bending vibrations in the absorption of wave number 852-846 cm −1 , which indicates the presence of β-14-glycosidic bonds.…”
Section: Discussionmentioning
confidence: 99%
“…Despite having numerous significant applications, the production routes of COS and GlcNAc are still in their infancy in terms of bio-sustainability. Currently, chemical processes are predominantly used for the production of COS and GlcNAc; however, degradation of product quality, generation of undesirable byproducts, and environmental concerns limits their application (Varun et al, 2017 ). Moreover, interest has been raised over enzymatic conversion (employing chitinase and/or N-acetyl glucosaminidase) of chitin and CHS to COS and GlcNAc that has the advantage of producing defined products with high specificity (Kumar et al, 2018a ).…”
Section: Introductionmentioning
confidence: 99%